(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study examines the formation and use of applied constructions in English and their significance in academic and professional texts. Applied constructions, including participial, gerundial, infinitival, and nominal structures, enhance cohesion, clarity, and expressive capacity by allowing complex ideas to be presented concisely and logically. The research highlights their role in specialized English instruction, particularly for learners in professional fields such as business, technology, construction, and architecture, where precise communication is essential. The findings indicate that contextualized teaching of applied constructions improves learners’ ability to produce coherent, accurate, and stylistically appropriate texts. Overall, mastering these constructions is crucial for achieving advanced language proficiency, facilitating professional and intercultural communication, and supporting effective text organization in various discourse contexts.